PARENTS' ASPIRATIONS AND PARTICIPATION IN CHILDREN'S EDUCATION: (STUDY ON THE COMMUNITY OF STANDARD TRADERS IN MANTAREN I VILLAGE PULANG PISAU) - Susan Daniel (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Human formation starts from childhood in the womb, which is then followed by the development of thechild after birth and grows into adulthood. Therefore, the role of the family, especially parents (fatherand mother) has a very important meaning, especially in the education of children. In this case, parentalparticipation is very necessary in supporting progress and education, because education is a sharedresponsibility between family, community and government, street vendors are one of the most tangiblejobs in most cities or developing countries in general. Street vendors are described as independententrepreneurs and the majority of them are unpaid workers. Its success is highly dependent on theeffort and ability to attract buyers. His parents are busy as traders, so the time for family is decreasing,this is because in their daily life they sell in the market or go around offering their wares. This research isone way to find out firsthand how the aspirations and participation of parents who have a profession asstreet vendors in the village area of Mantaren I Pulang Pisau towards children's education, as well asknowing firsthand how their need for education is to achieve equal distribution of education throughoutIndonesia. . This study uses a qualitative approach with descriptive analysis. The research subjects in thiscase were street vendors, both male and female along Jalan Desa Mantaren I Pulang Pisau, totaling 10people. Researchers took street vendors who already had 1 year of trading experience and who wereable to send their children to school. The instrument in this study consisted of the main instrument,namely the researcher himself and supporting instruments in the form of documentation, the datacollection procedure in this study was carried out using interview techniques so that it could be knowndirectly how the aspirations and participation of the subject towards children's education